A Comparative Study of Viral Hepatitis Infection Rates in Najaf Governorate, Iraq: (2023 vs. 2024) - Abd, Worood kadhim; Alwan, Amna Abbas; Hasan, Thualfakar Hayder (Medical Science Journal for Advance Research, 2025)
There is no information about the prevalence of hepatitis infection in the general population in Iraq because the political and social situation has not stabilized over the last decades. The most common cause of chronic liver disease is hepatitis B and C HBV and HCV infections are among the most common infectious diseases that affect human beings across the globe. The two infections have been linked to a wide constellation of clinical manifestations that include acute or fulminant hepatitis, chronic infection that may be clinically asymptomatic or may culminate in chronic hepatitis and liver cirrhosis. More than 20 million individuals are infected with hepatitis B per year around the world, and the estimated prevalence of chronic carriers of hepatitis B is 350 million individuals. In highly endemic regions, the hepatitis B virus is most frequently spread to the child by the mother at birth (perinatal transmission) or due to horizontal transmission (exposure to infected blood), especially when one child is infected and then transmits it to another uninfected child below the age of five years. Among the infants who are infected by their mothers or earlier than the age of five, chronic infection is widespread. The data of 590 patients infected with viral hepatitis C and B in 2023 and 620 patients with viral hepatitis C and B were collected from (Public Health Laboratory) in Al-Najaf as a center for all positive samples from all regions of Al-Najaf Governorate in Iraq (rural and city) with ages ranging from 1 to 80 years, males and females. Of the 590 infected patients in 2023, 392 had HBV infection, and 198 had HCV infection. Of 620 patients in 2024, 400 of them had HBV infection, and 220 of them had HCV infection.